Biological Applications of Biosilica/Silk Fibroin/Polyurethane (1:3:1) Composite - Supriya Prasad, P.; Gomathi, T.; Sudha, P.N.; Deepa, M.; Annie Kamala Florence, J.; Mubashirunnisa, A.; Latha, Srinivasan (Asian Journal of Chemistry, 2022)
High availability and several benefits of biosilica (BS) in various industries, it becomes a desirable material for industrial purposes. This study is focused to prepare a biocomposite of biosilica isolated from sugarcane baggase and combined with silk fibroin (SF) and polyurethane (PUF) foam. FTIR, XRD, TGA, DSC and SEM measurements were used to characterize the synthesized BS/SF/PUF biocomposite. The potentiality of biosilica composite as an antimicrobial support material was investigated. The BS/SF/PUF biocomposite has a rough surface nature, amorphous and higher thermal stability due to strong contacts, according to the characterization data. Furthermore, the results revealed that the produced material exhibited excellent antioxidant and antimicrobial properties.